2006
DOI: 10.1105/tpc.106.047605
|View full text |Cite
|
Sign up to set email alerts
|

ArabidopsisDCP2, DCP1, and VARICOSE Form a Decapping Complex Required for Postembryonic Development

Abstract: mRNA turnover in eukaryotes involves the removal of m 7 GDP from the 59 end. This decapping reaction is mediated by a protein complex well characterized in yeast and human but not in plants. The function of the decapping complex in the development of multicellular organisms is also poorly understood. Here, we show that Arabidopsis thaliana DCP2 can generate from capped mRNAs, m 7 GDP, and 59-phosphorylated mRNAs in vitro and that this decapping activity requires an active Nudix domain. DCP2 interacts in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
393
1
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(420 citation statements)
references
References 46 publications
18
393
1
8
Order By: Relevance
“…In animals, some of these complexes are associated with components of the RNA silencing machinery (Leung et al, 2006), and there is evidence that Drosophila P-bodies are involved in miRNA-directed target decay through deadenylation and decapping, whereas translational repression is P-body independent (Eulalio et al, 2007). In plants, components of the RNA decapping machinery were found involved in RNA silencing (Gazzani et al, 2004;Gy et al, 2007), and the existence of P-bodies was recently demonstrated (Xu et al, 2006). Thus, it will be interesting to investigate which type of proteins, such as other members of the large AGO family, are linked to miRNAs and their mRNA targets in nonpolysomal fractions.…”
Section: Discussionmentioning
confidence: 99%
“…In animals, some of these complexes are associated with components of the RNA silencing machinery (Leung et al, 2006), and there is evidence that Drosophila P-bodies are involved in miRNA-directed target decay through deadenylation and decapping, whereas translational repression is P-body independent (Eulalio et al, 2007). In plants, components of the RNA decapping machinery were found involved in RNA silencing (Gazzani et al, 2004;Gy et al, 2007), and the existence of P-bodies was recently demonstrated (Xu et al, 2006). Thus, it will be interesting to investigate which type of proteins, such as other members of the large AGO family, are linked to miRNAs and their mRNA targets in nonpolysomal fractions.…”
Section: Discussionmentioning
confidence: 99%
“…We selected heterozygotes and homozygotes of Arabidopsis mutant lines, dcp1-1 (GABI_844B03), 3 dcp1-2 (FLAG_563G05), 4 dcp2-1 (SALK_000519), 3,4 vcs-6 (SAIL_831_D08), 3 ago1-36 (SALK_087076), 23 se-1 (CS3176), 51 trs120-3 (SALK_111574), 42 hinkel (SAIL_1291_F04) and gnom (SALK_045424) by PCR-based genotyping. The primers used in the genotyping are listed in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…2A). 3,4,8 therefore, there was a possibility that the lethality caused the reduced levels of the miRNAs in the decapping mutants. To exclude this possibility, we examined the accumulation of the miRNAs in three other seedling lethal mutants (trs120, hinkel and gnom) by northern blotting.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations